Answer:where is the equation
Step-by-step explanation:
Simplify the following polynomial and write the answer in standard form.
(2x² - 4x + 3) + (x² - 4x-4)
A. -8x-1+3x^2
B. 3x^2 - 8x - 1
C. x^2 - 8x - 7
D. -8x - 7+x^2
Answer:
B)
Step-by-step explanation:
I solved it by setting it up as a normal addition problem:
[tex]2x^{2} -4x+3\\+x^{2} -4x-4[/tex]
Simplify:
[tex]3x^{2} -8x-1[/tex]
If a club consists of 11 members, how many different arrangements of president, vice-president, and secretary are possible?
There are 990 different arrangements of president, vice-president, and secretary
The number of arrangementsThe given parameters are:
Club members, n = 11
Members to arrange, r = 3
The number of arrangements is calculated using the following permutation equation
Ways = nPr
This gives
Ways = 11P3
Evaluate
Ways = 990
Hence, there are 990 different arrangements of president, vice-president, and secretary
Read more about permutation at:
https://brainly.com/question/12468032
Final answer:
To find the number of different arrangements of president, vice-president, and secretary in a club of 11 members, we use the concept of permutations. Using the formula for permutations of distinct objects, we calculate P(11,3) = 990. Thus, there are 990 different arrangements possible.
Explanation:
To find the number of different arrangements of president, vice-president, and secretary, we can use the concept of permutations. Since the positions have different roles and can only be assigned to one person each, we use permutations. The number of permutations can be found using the formula for permutations of distinct objects: P(n,r) = n! / (n-r)!.
In this case, we have 11 members and need to assign them to 3 different positions (president, vice-president, and secretary). So, the number of arrangements is P(11,3) = 11! / (11-3)! = 11! / 8! = 11 x 10 x 9 = 990.
Therefore, there are 990 different arrangements of president, vice-president, and secretary possible.
What is the surface area of the rectangular pyramid shown? 59.5 cm2 63 cm2 75.5 cm2 99 cm2
Answer:
Option D.
Step-by-step explanation:
In this question figure of pyramid is attached below the question .
Surface area of the rectangular pyramid :
Area of the Base = Length × Width
= 10 × 2 = 20 cm²
Area of Lateral #1 = [tex]\frac{1}{2}(P)(L)[/tex]
= [tex]\frac{1}{2}(10\times6.3)[/tex]
= 31.5 cm²
Area of Lateral #2 = [tex]\frac{1}{2}(8\times 2)[/tex]
= [tex]\frac{16}{2}[/tex]
= 8 cm²
Surface area of the pyramid = 20 + 2(31.5) + 2(8)
= 20 + 63 + 16
= 99 cm²
Surface area of the pyramid is 99 cm²
Answer:
99cm2
Step-by-step explanation:
Help will give brainliest to person who gets it right
Answer:
104
Step-by-step explanation:
Two shoes=20
Guy= 5
Glasses= 2
Boxing glove= 20
One shoe+guy with shoes, glasses, and gloves*glasses=104
Answer:
104
Step-by-step explanation:
60/3 = 20
Shoes = 20
30-20 = two weird people
two weird people = 10
one weird person = 5
9-5 = 4
two pairs of glasses = 4
one pair of glasses = 2
42 - 20 - 2 = 20
gloves = 20
shoe + (weird person + glasses + pair of shoes) x glasses = ?
10 + (5 + 2 + 20 + 20) x 2 = 20
10 + 47 x 2 = 104
10 + 94 = 104
I hope you understand this now!
The sum of two numbers is -36. One number is 106 less than the other. Find the numbers.
Answer:
71 and -35
Step-by-step explanation:
so with this we can set up a system of equations
x+y=36
and
x-y=106
now we can add these equations together to eliminate y
x+y=36 plus
x-y=106 equals
2x=142
divide both sides by 2
x=71
now we can plug that in
71+y=36
subtract 71 from both sides
y=-35
Answer:
-71 and
35
Step-by-step explanation:
Let the numbers be x and y
x + y = -36
x = y - 106
Substitute y - 106 or x in the first equation
We have
x + y = -36
y - 106 + y = -36
y + y - 106 = -36
2y - 106 = -36
Add 106 to both sides to eliminate -106 on the left side
2y - 106 + 106 = -36 + 106
2y = 70
Divide both sides by 2
2y/2 = 70/2
y = 35
Substitute 35 for y in either equation to get x
Using the second equation, we have
x = y - 106
x = 35 - 106
x = -71
The numbers are 35 and -71
Check
x + y = -36
-71 + 35 = -36
-36 = -36
The table represents the function f (x) = 5 x. A 2-column table with 4 rows. Column 1 is labeled x with entries negative 1, 0, 1, 2. Column 2 is labeled f (x) with entries blank, 0, 5, 10. Which value goes in the empty cell? –51 –5 5 51 Mark this and return
Final answer:
To find the value that goes in the empty cell, we need to multiply each value of x by 5. So, when x = -1, f(x) = 5*(-1) = -5. Therefore, the value that goes in the empty cell is -5.
Explanation:
The table represents the function f(x) = 5x. In the first column, we have the values of x, which are -1, 0, 1, and 2. In the second column, we have the values of f(x), which are blank, 0, 5, and 10. To find the value that goes in the empty cell, we need to multiply each value of x by 5. So, when x = -1, f(x) = 5*(-1) = -5. Therefore, the value that goes in the empty cell is -5.
Ms. Joseph is saving money for a trip to Zearnland over 12 weeks. She starts with 1 dollar. In the second week, she adds 2 dollars. Each week she adds 1 more dollar than she did the week before. For how many weeks will Ms. Joseph be saving money?
Ms. Joseph saves money for 12 weeks, starting with $1 and increasing the amount by $1 each week. By the 12th week, she adds $12. Therefore, she saves money for a total of 12 weeks.
To determine how many weeks Ms. Joseph is saving money, we need to look at the pattern of her savings. Each week, she adds one more dollar than the previous week:
Week 1: $1Week 2: $2Week 3: $3...Week 12: $12We can see that this is an arithmetic sequence where the first term (a) is $1 and the common difference (d) is $1. The nth term of an arithmetic sequence can be found using the formula: aₙ = a + (n-1)d.
For 12 weeks, the amount saved each week would be: a₁₂= 1 + (12-1) ×1 = 12. Ms. Joseph adds $12 in the 12th week. Finally, the total weeks she saves money is 12 weeks.
what is x+4x+6x= simplify
Answer:
11x
Step-by-step explanation:
What is g+1 when g= -9
Answer:
-8
Step-by-step explanation:
plug in -9 as g
(-9) + 1 = -8
Answer:
-8Step-by-step explanation:
If g = -9
Then g + 1 = -9 + 1
-9 + 1 = -8
I hope this helped you!
the vertical asymptote is at x =
Answer:
x=8
Step-by-step explanation:
The vertical asymptote is where the denominator goes to zero
3(x-8) =0
Divide by 3
(x-8) =0
Add 8 to each side
x-8+8=0+8
x=8
The vertical asymptote can be find by solving the 0 of the denominator.
3(x - 8) = 0
3x - 24 = 0
3x - 24 + 24 = 0 + 24
3x = 24
3x/3 = 24/3
x = 8
Besr of Luck!
Mya's lunchbox is shown. What is the volume of the lunchbox? Round to the nearest tenth if necessary.
There is no picture but the fomula for volume is lengthxwidthxheight for a square or rectangle
i need help solving 5x= -7x+6
Answer:
x=1/2
Step-by-step explanation:
1.). add 7x to both sides
12x=6
2.) divide by 12 to get x by itself.
x=6/12
3.) simplify the fraction and you get the answer!
x=1/2
Find the indicated side of the right triangle
Answer:
[tex] \tan(30) = \frac{7}{x} [/tex]
[tex] \frac{1}{ \sqrt{3} } = \frac{7}{x} [/tex]
[tex]x = 7 \sqrt{3} [/tex]
Answer:
7 * sqrt(3) =x
Step-by-step explanation:
Since this is a right triangle, we can use trig functions
tan theta = opp/ adj
tan 60 = x/7
Multiply each side by 7
7 tan 60 =x
We know than 60 =sqrt(3)
7 * sqrt(3) =x
You are having 14 people for brunch and each person will eat 2 muffins how many muffins do you need the recipe makes 12 muffins
Answer: what’s the recipeeeeeee we need the recipe to answer the question
Step-by-step explanation:
Answer:
You would need to bake 3 batches of 12 muffins for a total of 36.
Step-by-step explanation:
If you have 14 people that will each eat 2 muffins, a total of 28 muffins are needed. Since the batches make 12, 2 batches wouldn't be enough. It's always better to round up for these questions. Hope this helps! :)
X^2-81
Factor the quadratic completely
Answer:
x ^2 − 9^ 2. hope this helps
Answer:
(x+9)(x-9)
Step-by-step explanation:
whenever its is x^2
you can start off with
(x+_)(x+_)
then your figure out "what times what" is -81 (they have to be the same number!)
Its -9 and 9
and so you plug that in to get
(x+9)(x-9)
Which of the following is equivalent to | − 12 + 3 | ?
The equivalent of the expression | - 12 + 3 | is 9 because after simplifying the expression inside the absolute value parentheses, -12 + 3 is -9 and the absolute value of -9 is 9.
Explanation:The student is asking for the equivalent of the absolute value expression | − 12 + 3 |. To solve this, we have to simplify the expression inside the absolute value parentheses first, which means performing the operation −12 + 3. This results in −9, because when you add a positive number to a negative one, you effectively subtract the smaller number from the larger one, but keep the sign of the larger number.
The absolute value of a number is the distance of that number from zero on a number line, regardless of the direction, so the absolute value of −9 is 9. Therefore, the expression | − 12 + 3 | is equivalent to 9.
Learn more about Absolute Value here:
https://brainly.com/question/4691050
#SPJ3
In a video game, the player can choose a character from 4 animal characters and 3 huma
characters. Players can also let the computer randomly select a character for them.
The player will have the computer randomly select his character.
What is the probability it will pick a human character?
Enter your answer as a fraction, in simplest form, in the box.
Will mark brainliest!!
Answer:
3/7
Step-by-step explanation:
3/(3+4)
BRAINLIEST PLZ I ANSWERED FIRST
Answer:
3/7
Step-by-step explanation:
Probability is essentially (# ways specific event can occur) / (# ways any general event can occur).
In this case, the specific event is getting a human avatar. Since there are 3 humans to choose from, the number of ways this specific event can occur is 3 ways. The general event is just choosing any avatar. Since there are a total of 3 + 4 = 7 characters to select from, the number of ways this general event can occur is 7.
Putting it together, we have the probability of choosing a human character as 3/7.
At noon (12:00), Annette rented a bicycle to travel around Stanley Park. She returned the bicycle at 4:00 pm (16:00) the same day after travelling 48 km. It cost $22 to rent the bicycle.
a. Determine Annette’s average speed in km/hr.
b. Determine the rental rate in dollars per hour. Round your answer to 2 decimal places.
c. Determine the rental rate in dollars per km. Round your answer to 2 decimal places.
Answer:
a. average speed is 12km/hr
b. $5.50 dollars per hour
c. $0.46 per km
Step-by-step explanation:
a. 48km/4hrs = 12km/hr
b. $22/4hrs = $5.50/hr
c. $22/48km = $0.45833/km rounded to $0.46/km
What’s the answer to Y=-2(x-3)^2+1
Answer:
Step-by-step explanation:
Y= -2(x - 3)^2 + 1 can be seen as the equation of a parabola with vertex at (3, 1) and which opens down.
Y= -2(x - 3)^2 + 1 could also be expanded, obtaining a formula for the same parabola but in different format:
y = -2(x^2 - 6x + 9) + 1, or
y = -2x^2 + 12x -18 + 1, or y = -2x^2 + 12x - 17
f(n)=41-5n
complete the recursive formula of f(n)
f(1)=
f(n)=f(n-1)+
The recursive formula for f(n) = 41 - 5n is f(1) = 36 and f(n) = f(n-1) - 5, with f(n) being found by subtracting 5 from the previous value of f(n).
Explanation:The function f(n) = 41 - 5n is a linear function, where n is the input. The recursive formula for this function can be defined as follows:
f(1) = 41 - 5*1 = 36f(n) = f(n-1) - 5
The second formula is saying that to find the value of the function at n, subtract 5 from the value of the function at the previous value of n.
Learn more about Recursive Formula here:https://brainly.com/question/32794966
#SPJ12
The recursive formula for f(n) = 41 - 5n is f(1) = 36 and f(n) = f(n-1) - 5, with f(n) being found by subtracting 5 from the previous value of f(n).
The base of a triangular prism is an isosceles right triangle with a hypotenuse of 72−−√ centimeters. The height of the prism is 7 centimeters. Find the surface area of the triangular prism. Round your answer to the nearest tenth.
Answer:
Step-by-step explanation:
Surface area = lateral area + 2(area of base)
Lateral area = perimeter of base * height.
Because it is a isosceles right triangle, both sides are equal.
[tex]x^{2} +x^{2}[/tex] = 72
2[tex]x^{2}[/tex] = 72. Divide both sides by 2
[tex]x^{2}[/tex] = 36. Square both sides.
x = 6.
So the perimeter of the base = 6 + 6 +[tex]\sqrt{72}[/tex] = 20.485281374239
Lateral area = 20.485281374239 * 7 = 143.397 [tex]cm^{2}[/tex]
Area of base is (1/2)base * height.
(1/2)(6)(6) = 18
Using the surface area formula
surface area = 143.397 + 2(18) = 179.4 [tex]cm^{3}[/tex]
Final answer:
The surface area of the triangular prism can be calculated by finding the areas of the two triangular bases and the three rectangular sides. After calculations, the total surface area of the prism is found to be 2304 square centimeters.
Explanation:
The question asks us to find the surface area of a triangular prism whose base is an isosceles right triangle with a hypotenuse of √72 centimeters and a height of 7 centimeters. We'll use various formulas for geometry, area, and volume to solve this problem.
First, we need to find the legs of the isosceles right triangle which form the base of the prism. Since it is a right triangle, and the legs (a) are equal, we can use Pythagoras' theorem where [tex]a^2 + a^2 = (72)^2[/tex]
Solving this gives us each leg as 36 cm.
The area of the base triangle is then found using 1/2 × base × height, which gives us-
1/2 × 36 × 36 = 648 square centimeters
The prism has two such triangular bases, so their combined area is 2 × 648 = 1296 square centimeters.
For the three rectangular sides, we calculate their areas by using the formula for the area of a rectangle (length × width). Each side has a length of 7 cm (the height of the prism). The widths are equal to the sides of the triangular base: 36 cm, 36 cm, and √(362 + 362) = √2592 = 72 cm. Thus, the total area of these sides is-
2(36 × 7) + (72 × 7) = 504 + 504 = 1008 square centimeters.
The total surface area of the prism is the sum of the areas of the bases and the rectangular sides, which is 1296 + 1008 = 2304 square centimeters.
I'm really stuck on this question and if anyone could help me with it I'd be so grateful
Answer:
150
Step-by-step explanation:
Rate at which volume decrease:
(1 × 2 × 20/100) ÷ 30
= 1/75 m³/min
Total volume:
½ × (1.4 + 0.6) × 2 × 1
= 2 m³
Time = 2 ÷ 1/75
= 150 mins
A recipe for cake needs 2 and 1/4 cups of cake mix. You are making ½ of the recipe. How many cups of flour do you need?
Answer:
x=1 1/8
Step-by-step explanation:
1 cake=2 1/4 cup of cake
1/2 cake=x
1 cake=9/4 cup of cake
1/2 cake= x
Cross multiply
x=9/4×1/2
x=9/8
X=1 1/8
Final answer:
To make ½ of a cake recipe that calls for 2 and ¼ cups of cake mix, you need to divide that amount by 2, resulting in 1 and 1/8 cups of cake mix needed.
Explanation:
To find out how many cups of cake mix you need to make ½ of the recipe, start with the original amount of cake mix required by the recipe, which is 2 and ¼ cups. Since you're making half of the recipe, you'd divide this amount by 2. Perform the division: (2 + ¼) ÷ 2 = 1 and ¹⁸ cups. Thus, you will need 1 and ¹⁸ cups of cake mix for half the recipe.
Here's the step-by-step calculation:
Convert the mixed number to an improper fraction: 2 and ¼ cups = 9/4 cups.
Divide the improper fraction by 2 to make half of the recipe: (9/4) ÷ 2 = 9/4 × 1/2 = 9/8.
Convert the improper fraction back to a mixed number: 9/8 = 1 and 1/8 cups.
So, you need 1 and 1/8 cups of cake mix to make half of the recipe.
A swimming pool had 2.5 million liters of water in it. Some water evaporated, and then the pool only had 2 million liters of water in it.
What percent of the water evaporated?
25 % of the water had evaporated.
Answer:
20%
Step-by-step explanation:
Since the total amount of water is 2.5 million
And 2 million evaporated,
To determine the amount left,it will be total amount- evaporated
2.5-2=0.5
To determine the% of evaporated water
It will be evaporated/total amount ×100
0.5/2.5 × 100
50/2.5
20%
So the percentage of the evaporated water is 20%
What is X if Y is 12.8 and Z is 16 in the right triangle below?
Answer:
Im 90% sure its H.
Step-by-step explanation:
Answer:
H) 9.6
Step-by-step explanation:
Use the pythagorean theorem to solve for a right triangle.
Pythagorean Theorem: a^2 + b^2 = c^2
So, 16^2= 12.8^2 + x ------> 256= 163.84 + x^2 (subtract 163.84 from both sides of the equation) -----> x^2= 92.16 (square root) -----> x=9.6
This is my first answer so I hoped it helped! :)
please help me solve this
Answer: 10
10 squared
10 cubed
Answer:
Step-by-step explanation:
to evaluate for your questions in the power of 10
1) 624 ÷ 10 = 62.4..................................... 10
2) 624 ÷ 100 = 6.24 ............................................... 10²
3) 624 ÷ 1000 = 0.624 .........................................10³
Jimmy rolls a number cube multiple times and records the data in the table above. At the end of the experiment, he counts that he had rolled 140 fives. Find the experimental probability of not rolling a five, based in Jimmy’s experiment. Round the answer to the nearest thousandth.
A. 0.140
B. 0.167
C. 0.667
D. 0.860
Answer: D. 0.860
Step-by-step explanation:
In the table we can see that he rolled the cube 1000 times, and he recorded that 140 of those times he rolled a 5.
Then, the probability of rolling a 5 will be equal to:
P1 = 140/1000 = 0.14
Now, the probabilty of NOT rolling a 5, is equal to the rest of the probabilities, this is:
P2 = 1 - 0.14 = 0.86
then the correct option is D
What is 5u+1 when u=3
select all that are true for the graph that represents the function f(x)=5(3)^x
Answer:A. The graph is increasing by a common ratio of 3
C. As x increases, y increases
F. As x decreases, y approaches 0
Step-by-step explanation:
The true statements are:
A. The graph is increasing by a common ratio of 3
C. As x increases, y increases
F. As x decreases, y approaches 0
Information regarding the function:The graph should be rise by ratio of 3. Since x increased so y should also rises. Also, x reduced so y should be 0.Therefore, the option A, C and F is correct. And the other options are incorrect.Find out more information about the graph here: https://brainly.com/question/14375099?referrer=searchResults
Use the graph of f(x) to explain the relationship between the real zeros of f(x) and its intercept(s). f(x) has one real zero at –2 because the graph of the function has an intercept at (0, –2). f(x) has two real zeros at –4 and –2 because the graph of the function has intercepts at (–4, 0) and (0, –2). f(x) has no real zeros because the graph of the function does not pass through (0, 0). f(x) has one real zero at –4 because the graph of the function has an intercept at (–4, 0).
Answer:
f(x) has one real zero at –4 because the graph of the function has an intercept at (–4, 0).
Step-by-step explanation:
Zeros of a function f(x) are those points where f(x) = 0. Then, zeros coordinates have the form (x1, 0), (x2, 0), et cetera. In the graph, a zero is seen as the interception of f(x) with the x-axis.
Answer:
D on Edge 2020
Step-by-step explanation: